Pemanfaatan Limbah Kayu Menjadi Produk Bernilai Ekonomi: The Utilization of Wood Waste Becomes Products of Economic Value - Mahdie, Muhammad Faisal; Sari, Noor Mirad; Violet, Violet; Nisa, Khairun; Rani, Syahrul; Hidayatullah, Muhammad; Misin, Misin (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Wood waste is the remains of wood parts no longer considered economically valuable in product processes. However, if wood waste products are made at different times and places, they will produce new economic value products. Waste wood pieces are currently not utilized optimally due to the lack of knowledge and insight into technology and the development of creativity in the community regarding the use of wood waste. Partners in PKM are the SUKAYU (Suka Karya Kayu) group, which has just started a business with limited wood products, namely, placing flower pots. The problem partners face is limited knowledge, skills, equipment, and capital, so they cannot develop product innovations based on the high selling value and artistic value of wood waste. The method used is training on making chairs, shoe racks, and flower pots using applicative methods, mentoring, and evaluating activities. Training program held on August 16, 2022. After the training, there was an increase in the partners' knowledge and skills about wood waste and its use as wood products, and the partners were able to make several wood products from the waste. The outputs of the Community Partnership Program activities are wood products (chairs, shoe racks, and flower pots), publications in The Banjarmasin Post Online, scientific articles, and activity videos on YouTube.